TAFSIR AL-AZHAR: SUATU TINJAUAN BIOGRAFIS DAN METODOLOGIS - Malkan, Malkan (Hunafa: Jurnal Studia Islamika, 2009)
This article deals with Tafsîr al-Azhâr from biographical and methodological perspectives employing historical method. Hamka started writing this Tafsîr al-Azhâr  in 1959 than convoyed it as a down lecture in the Mosque of al-Azhâr. He completed the writing of this book of al-tafsîr when he was  being jailed. This book of al-tafsîr consists of thirty chaptersl. After analyzing the contents of the book of al-tafsîr, the writer found that Hamka employed rational method with literature and social patterns based on the school of Islamic orthodoxy and Islamic free act.Kata Kunci:    Hamka, Tafsîr al- Azhâr, tafsir bi al-ma'tsur,  tafsir bi al-ra'y, metode tahlilî,  corak penafsiran adabî, corak penafisran ijtimâ’î